2009
DOI: 10.1111/j.1747-4949.2009.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Units: Many Questions, Some Answers

Abstract: Stroke units are cost-effective and need to be considered as a priority in health-care provision for stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 92 publications
(109 reference statements)
0
15
0
14
Order By: Relevance
“…Every stroke patient can potentially benefit from care in a stroke unit. These units usually are efficient, cost-effective, and their benefits are consistent over time 10 . A Canadian cohort showed that initial assessment by a stroke team reduced stroke case fatality at 7 days, 30 days and 1 year 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Every stroke patient can potentially benefit from care in a stroke unit. These units usually are efficient, cost-effective, and their benefits are consistent over time 10 . A Canadian cohort showed that initial assessment by a stroke team reduced stroke case fatality at 7 days, 30 days and 1 year 11 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the patients who showed a large difference between the rSO 2 values of the diseased hemisphere when compared with the 'healthy' hemisphere had a better outcome. Also, a narrowing of the interhemispheric rSO 2 difference heralded increased swelling, while decompression (by hemicraniectomy) yielded a larger difference in rSO 2 , with positive values on the infarcted side. While the physiological explanation of increased oxygen saturation (rSO 2 ) on the infarcted side may be surprising, and the assessment of rSO 2 values with different monitors has been debated [83,84], the application of oxygenation and CBF parameters by non-invasive OI in patients with malignant stroke seems promising, especially when considering the complicated decision algorithm for invasive therapy [85].…”
Section: (B) Monitoring Malignant Strokementioning
confidence: 99%
“…the last decade has seen major advances in the management of acute stroke. This is largely due to two therapeutic inventions that have been established to improve outcome: causal therapy of the focal ischaemia by thrombolysis [1] and (sub)acute monitoring of patients in specialized stroke units [2,3]. While the focus on the (sub)acute phase of stroke is beneficial beyond doubt, the burden caused by stroke by far outlasts this acute stage.…”
Section: Introductionmentioning
confidence: 99%
“…Son estructuras geograficamente delimitadas con monitorización continua no invasiva, con personal entrenado y coordinado por neurólogos que dirigen un equipo multidisciplinario. Han demostrado, con un nivel de evidencia I, que mejoran la morbimortalidad con un equilibrio coste/eficacia favorable, y reducen las complicaciones y la dependencia 3,4 . La Declaración de Helsinborg, un consenso paneuropeo para el manejo del ictus, recoge que las UI constituyen el cuidado mas efectivo del ictus y la intervención con mayor beneficio comunitario y superan claramente a la trombólisis.…”
unclassified
“…La mayoría de los pacientes que han presentado un ictus se benefician de las UI. Por el contrario, el ingreso en una UCI no es eficiente, ya que la inmensa mayoría de los pacientes no precisan este tipo de cuidados 4 .…”
unclassified